Tingkat Kinerja Penyuluh Pertanian di Kabupaten Konawe Provinsi Sulawesi Tenggara - Syafruddin Syafruddin; Sunarru Samsi Hariadi; Sri Peni Wastutiningsih (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
This study aims to provide information on the level of performance of agricultural extension Konawe Southeast Sulawesi and the factors that influence. The unit of analysis This study is of agricultural extension, taken/withdrawn in census namely throughout civil servants of agriculture extension worker of the research sites (130 people), while of the objectivity to assess the performance of agricultural extension also taken two farmers who are in the target area so that the number of agricultural extension farmers is 260 people. Data of results in research the analysis use the proportion test, with the provision that the largely the performance level of agricultural extension (> 50 %) in the category which low. Based on the results obtained by the analysis of the proportion test of Z count value as big as -7,89 is smaller than the Z table at 5% confidence level is equal to 1.960, then the research hypothesis which states that most of the agricultural extension worker number (> 50 %) have in low performance level is rejected, because the reality shows that the level of performance of agricultural extension who are being.Keywords: Performance, level, agricultural, extension